Forest And Land Fire Management Strategies : Prevention And Law Enforcement - Mohammad Solekhan; Kunarto; Mahmuda Pancawisma Febriharini (CV. Inara, 2022)
Forest and land fires are hot topics discussed in both the mass media and electronic media. Forest and land fires have a huge impact on the economy and public health. Another impact of forest fires is the loss of various ecosystem benefits contained in the forest, flora and fauna, as well as other potentials contained therein, including biodiversity. The purposes of this paper are: (1) to identify and describe the strategies implemented by the government in an effort to reduce the occurrence of forest and land fires; (2) to know and describe the law enforcement carried out in dealing with forest fires. The results that can be obtained are the strategies that can be used to overcome forest and land fires carried out by the government are: by providing education to the public about the impacts that can be caused by forest and land fires, as well as providing infrastructure assistance in overcoming forest and land fires. Meanwhile, law enforcement against companies or corporations that carry out forest and land fires is still considered very weak and has not run optimally in accordance with the wishes of the law itself. The conclusion is that although the government has taken steps to deal with forest fires, if no action is taken to give sanctions to the perpetrators of forest and land burning, then everything will not work, especially for forest and land burning carried out by companies or corporations.